2008
DOI: 10.1093/nar/gkn1050
|View full text |Cite
|
Sign up to set email alerts
|

The G140S mutation in HIV integrases from raltegravir-resistant patients rescues catalytic defect due to the resistance Q148H mutation

Abstract: Raltegravir (MK-0518) is the first integrase (IN) inhibitor to be approved by the US FDA and is currently used in clinical treatment of viruses resistant to other antiretroviral compounds. Virological failure of Raltegravir treatment is associated with mutations in the IN gene following two main distinct genetic pathways involving either the N155 or Q148 residue. Importantly, in most cases, an additional mutation at the position G140 is associated with the Q148 pathway. Here, we investigated the viral DNA kine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

20
130
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 129 publications
(151 citation statements)
references
References 23 publications
20
130
1
Order By: Relevance
“…The double mutation conferred significant resistance to both compounds, as the EC 50 s of RAL and EVG were about 1.9 M and 2.3 M, respectively (FC values, 241 and 1,762, respectively; Table 1). These results are fully consistent with those of previous studies that concluded the secondary G140S change increased the overall level of resistance to RAL conferred by the primary Q148H mutation and repaired an inherent IN catalytic defect (6,26). Moreover, they established our ability to detect relatively large FCs in sensitivity to INSTIs ( Table 1).…”
supporting
confidence: 92%
“…The double mutation conferred significant resistance to both compounds, as the EC 50 s of RAL and EVG were about 1.9 M and 2.3 M, respectively (FC values, 241 and 1,762, respectively; Table 1). These results are fully consistent with those of previous studies that concluded the secondary G140S change increased the overall level of resistance to RAL conferred by the primary Q148H mutation and repaired an inherent IN catalytic defect (6,26). Moreover, they established our ability to detect relatively large FCs in sensitivity to INSTIs ( Table 1).…”
supporting
confidence: 92%
“…At this point, all available data suggest that N155H variants are preferentially selected early in RAL treatment failure but are subsequently replaced by variants containing other primary mutations after the further acquisition of secondary mutations under RAL pressure (26). The later emergence of Q148H variants is also consistent with the observation that this mutation impairs integration which can be rescued by the addition of a G140S mutation (6). Based on our survey of 200 clinical isolates, single substitution Q148H variants were rarely observed in vivo and, when identified, rapidly acquired G140S.…”
Section: Discussionsupporting
confidence: 63%
“…3). In HIV-1, the relative viral fitness of IN mutant viruses in competition with WT showed that Q148R resulted in a reduction in viral fitness to ϳ59% of WT levels, while N155H caused only a 24% reduction in relative fitness (52)(53)(54). The addition of the G140S mutation to Q148R diminished replication capacity to levels similar to those seen for Q148R-mutated HIV-1 (59% of WT levels) (54).…”
Section: Discussionmentioning
confidence: 82%